2018
DOI: 10.1101/408013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A simian-adenovirus-vectored rabies vaccine suitable for thermostabilisation and clinical development for low-cost single-dose pre-exposure prophylaxis

Abstract: BackgroundEstimates of current global rabies mortality range from 26,000 to 59,000 deaths per annum. Although pre-exposure prophylaxis using inactivated rabies virus vaccines (IRVs) is effective, it requires two to three doses and is regarded as being too expensive and impractical for inclusion in routine childhood immunization programmes.Methodology/ Principal FindingsHere we report the development of a simian-adenovirus-vectored rabies vaccine intended to enable cost-effective population-wide pre-exposure pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…We have now dried full human doses (5×10 10 virus particles, approximately 5×10 8 infectious units [IU]) of a simian adenovirus vectored rabies vaccine (ChAdOx2 RabG) upon 1 cm 2 of the matrix, with <0.1 log 10 -fold loss in-process (i.e. during desiccation) and approximately 0.3 log 10 -fold loss after thermochallenge at 30°C for a month (Figure 1C) 28 . For explanation of the log 10 -fold loss metric, please see Methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have now dried full human doses (5×10 10 virus particles, approximately 5×10 8 infectious units [IU]) of a simian adenovirus vectored rabies vaccine (ChAdOx2 RabG) upon 1 cm 2 of the matrix, with <0.1 log 10 -fold loss in-process (i.e. during desiccation) and approximately 0.3 log 10 -fold loss after thermochallenge at 30°C for a month (Figure 1C) 28 . For explanation of the log 10 -fold loss metric, please see Methods.…”
Section: Resultsmentioning
confidence: 99%
“…Simian adeno virus vectors ChAd63-METRAP and ChAdOx2-RabGP were prepared, purified and tested for quality by the Jenner Institute Viral Vector Core Facility, as previously described 28, 29 . Viruses were dialysed against either a previously used storage buffer (10mM Tris, 7.5 % w/v sucrose, pH 7.8) or unbuffered 0.5M trehalose and sucrose and stored at −80°C as stock.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most human cases of rabies are the result of dog bites (Fooks et al, 2017) . There is a strong argument for investment in dog vaccination: the feasibility and cost-effectiveness of rabies control and human rabies elimination by dog vaccination has been demonstrated in some countries (Wang, C. et al, 2018) . Several inactivated preparations of RABV are available as vaccines to immunize humans and domestic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Not only inactivated vaccines, but also other recombinant vaccines trials are reported elsewhere. Recently, a simian adenovirus-vectored candidate showed that single-dose vaccination induced strong neutralizing antibodies in mice (Wang, C. et al, 2018) . Also, other rabies vaccine candidates using viral vectors have been reported (Abreu-Mota et al, 2018;Chen et al, 2019;Ramya et al, 2011;Wang, X. et al, 2019) .…”
Section: Discussionmentioning
confidence: 99%